Unending Conflict in Kashmir: Historical Analysis - Rizwan Ali (ASIAN Journal of International Peace & Security (AJIPS), 2021)
The Kashmir region is the center of major disputes in South Asia. Peace and cooperation of the entire region have been dependent on its resolution. Kashmir takes central importance because it can be both the pulling and the pushing factor for peace, stability, and cooperation in South Asia. It is a disputed land by all three countries but aggressively by Pakistan and India. It is also the subject of perpetual struggle, pushing each country to spend billions of dollars on Kashmir-oriented issues. The dispute over Kashmir has remained the bone of contention. This paper is based on primary data and secondary data. The primary data was collected from legislatures, political activists, people from academia and a contractor who worked on the Line of Control (LoC). This paper highlights the history of the dispute over Kashmir, the contemporary issues and policies circling Kashmir, development and human rights violations, the role of international organizations, and economic costs of the conflict over Kashmir incurred by both countries.